2020
DOI: 10.2217/bmm-2019-0608
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Hub Genes and Discovery of Promising Compounds in Gastric Cancer Based on Bioinformatics Analysis

Abstract: Aim: To explore the mechanism of gastric carcinogenesis by mining potential hub genes and to search for promising small-molecular compounds for gastric cancer (GC). Materials & methods: The microarray datasets were downloaded from Gene Expression Omnibus database and the genes and compounds were analyzed by bioinformatics-related tools and software. Results: Six hub genes ( MKI67, PLK1, COL1A1, TPX2, COL1A2 and SPP1) related to the prognosis of GC were confirmed to be upregulated in GC and their high expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…HJURP [65], CENPA [66], PLK1 [67] and IFI6 [68] were found to significantly increase in gastric cancer tissues compared with normal tissues. In addition, HJURP [69], PLK1 [58], MKI67 [70] and IFI6 [71] have been identified as potential therapeutic target for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…HJURP [65], CENPA [66], PLK1 [67] and IFI6 [68] were found to significantly increase in gastric cancer tissues compared with normal tissues. In addition, HJURP [69], PLK1 [58], MKI67 [70] and IFI6 [71] have been identified as potential therapeutic target for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 85%
“…A study of peripheral blood transcriptome sequencing in patients with pneumonia found that the expression of UBE2C in patients with severe pneumonia was higher than that in patients with mild pneumonia[64]. HJURP[65], CENPA[66], PLK1[67] and IFI6[68] were found to significantly increase in gastric cancer tissues compared with normal tissues. In addition, HJURP[69], PLK1[58], MKI67[70] and IFI6[71] have been identified as potential therapeutic target for COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…As the development of new drugs is a time-consuming and high-risk process, in this case, through gene expression profile technology to find anti-IBC drug targets, the use of drug repositioning technology to explore the novel efficacy of existing drugs, so as to achieve “new uses of old drugs,” which has become an effective measure to improve the input-output ratio of drug development and reduce the risk of failure [ 35 ]. In our study, ten candidate small molecular compounds were identified via CMap database.…”
Section: Discussionmentioning
confidence: 99%
“…Bioinformatics tools provide extensive technical support for the processing and analysis of gene expression profiles. As a result, bioinformatics analysis has been widely used in recent years to identify novel therapeutic targets and diagnostic markers [37]. In this study, four GEO datasets related to IBDs, GSE156044, GSE159008, GSE102746 and GSE159751, were examined using the Limma package in R statistical software and 368 DEGs were identified.…”
Section: Discussionmentioning
confidence: 99%